Studies on gasification of corncobs and its utilization - Allen, Deuel H.
The endeavor to expand the energy based led to several studies on the utilization of offals from agriculture and forest products. Although there were studies on the utilization of ipil-ipil wood, charcoal, coconut shells, coir fibers and rice husks, most of them tried to study ways and means of efficiently converting biomass into salable energy in the form of producer gas.